Transient Hypothyroxinaemia in Full Term Low Birth Weight Neonates (Journal of Armed Forces Medical College, Bangladesh, 2010)
This prospective study was done in Combined Military Hospital, Dhaka from July 2002 to June 2003 todocument the postnatal changes of thyroid hormones in full term low birth weight (LBW) neonates. Theparameters were- serum TT4 (total thyroxin), TT3 (total triiodothyronine), FT4 (free thyroxin) and TSH(thyroid stimulating hormone). Twenty seven healthy full term neonates formed the control group (group A)who were studied on day 5 to observe the base line data. Study group (group B) consisted of 27 low birthweight (LBW) neonates. They were studied twice on day 5 (B1) and day 45 (B2). The mean ± SD gestational agewas 38.41±0.93 and 38.63±1.08 weeks in group A and B respectively. The mean ± SD birth weight were3.41±0.55 and 2.11±0.33 kg in group A and B respectively and the difference was statistically significant (p